코넥스(KONEX: Korea New Exchange) 시장 활성화 조치: 효과 및 시사점 - 김명애; 우민철 (Asia-Pacific Journal of Business Venturing and Entrepreneurship, 2017)
KONEX (Korea New Exchange) is the organised stock exchange for small enterprises. It is a channel through which venture start-ups at their early stage can raise funds without a huge burden of debt. We explain the regulations in this market and examine the effects of major changes in the relevant regulations. The first change was replacing the call auction mechanism with the continuous auction mechanism. The change improved the information asymmetry among investors. The second was lowering the minimum deposit requirement for individual investors from 300 million won to 100 million won. As the result of the change, market liquidity increased a lot and the number of investors increased. The last change was introducing the small investment account. Although this raised the participation of individual investors but did not lead to the improvement in market liquidity or information asymmetry. In overall, encouraging more investors to participate in the transactions in KONEX is the fast way to boost the market, while the long-term strategy should focus more on improving the information asymmetry by helping information generating and transferring activities. 코넥스시장은 초기 중소, 벤처기업들이 거래소시장에 주식을 상장할 수 있게 함으로써 과다한 부채를 부담하지 않으면서 필요한 자금을 조달할 수 있게 하는 통로이다. 본 연구는 코넥스시장의 주요 제도들을 설명하고 이와 관련하여 그동안 꾸준히 시도해온 시장활성화 대책들의 효과를 분석하였다. 코넥스시장의 활성화를 위한 첫 번째 대책으로서 단일가매매를 접속매매로 변경한 조치의 경우에, 정보비대칭 개선 효과가 있는 것으로 나타났다. 두 번째, 투자위험 감당능력이 낮은 투자자의 시장진입을 제한하는 제도인 기본예탁금 요구수준을 기존의 3억 원에서 1억 원으로 낮춘 조치의 결과로 시장유동성이 현저히 향상되었고 시장참여자의 수가 증가했다. 마지막으로, 소액투자전용계좌 도입 조치는 개인투자자의 시장참여 정도를 높였으나 시장유동성 및 정보비대칭 개선으로 이어지지 않은 것으로 나타났다. 분석결과를 종합할 때, 투자자범위제한 축소 조치를 통해 다양한 투자자의 활발한 시장 참여를 유도하는 것이 조속한 시장활성화에 가장 효과적인 한편, 소액투자자 증가에 대비하여 상장주식에 대한 정보생성 통로를 강화함으로써 정보비대칭을 완화하는 것이 장기적으로 창업기업의 직접금융시장에서의 조달비중 확대를 꾀할 수 있는 방안임을 시사한다.